Modified polytetrafluoroethylene
By introducing an appropriate amount of chloroethylene trifluoroethylene units into the polytetrafluoroethylene and controlling the polymerization conditions, the contradiction between the breaking strength and the extrusion pressure during the extrusion process is solved, and the effect of high breaking strength and low extrusion pressure is achieved.
Patent Information
- Application Number
- CN202380057981.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-08-10
- Filing Date
- 2023-08-10
- Publication Date
- 2025-03-18
AI Technical Summary
There is a contradiction between the fracture strength and the extrusion pressure during the extrusion process of existing modified polytetrafluoroethylene, which is difficult to simultaneously increase the fracture strength and reduce the extrusion pressure.
By introducing chloroethylene trifluoroethylene units into tetrafluoroethylene and controlling polymerization conditions, a modified polytetrafluoroethylene containing tetrafluoroethylene and chloroethylene units was prepared to ensure that the proportion of the amount of chloroethylene units in all polymerization units is 1.0 mass % or less.
Modified polytetrafluoroethylene, which has a high fracture strength but low extrusion pressure, is achieved, improving the moldability and processability of the material.
Smart Images

Figure BDA0005262118070000171
Abstract
Description
Technical Field
[0001] The present invention relates to modified polytetrafluoroethylene. Background Art
[0002] When polytetrafluoroethylene is highly stretched in the unfired state, a porous polytetrafluoroethylene membrane can be obtained. This porous membrane allows gases such as water vapor to pass through, but due to the strong water repellency of polytetrafluoroethylene, water droplets cannot pass through. This unique property is used in clothing, separation membranes, etc.
[0003] Patent Document 1 describes a modified tetrafluoroethylene polymer obtained by a predetermined production method using chlorotrifluoroethylene as a modifier in order to improve paste extrudability.
[0004] Patent Documents 2 to 4 describe tetrafluoroethylene homopolymers and modified polytetrafluoroethylene having units based on perfluoro(propyl vinyl ether) and hexafluoropropylene, which are used for stretching.
[0005] Prior art literature
[0006] Patent Literature
[0007] Patent Document 1: Japanese Patent Application Laid-Open No. 51-36291
[0008] Patent Document 2: Japanese Patent Application Publication No. 2000-143707
[0009] Patent Document 3: International Publication No. 2007 / 046345
[0010] Patent Document 4: International Publication No. 2010 / 113950 Summary of the invention
[0011] Technical problem to be solved by the invention
[0012] The object of the present invention is to provide a modified polytetrafluoroethylene which has a low extrusion pressure despite a high breaking strength.
[0013] Solutions to technical problems
[0014] The present invention (1) is a modified polytetrafluoroethylene which is stretchable and comprises tetrafluoroethylene units and chlorotrifluoroethylene units, wherein the amount of the chlorotrifluoroethylene units is 1.0% by mass or less based on the total polymer units.
[0015] The present invention (2) is the modified polytetrafluoroethylene described in the present invention (1), which has a breaking strength of 20.0N or more.
[0016] The present invention (3) is the modified polytetrafluoroethylene described in the present invention (1) or (2), wherein the extrusion pressure is 5 MPa or more.
[0017] The present invention (4) is a modified polytetrafluoroethylene in combination with any one of the present inventions (1) to (3), wherein the extrusion pressure is 50 MPa or less.
[0018] The present invention (5) is a modified polytetrafluoroethylene in combination with any one of the present inventions (1) to (4), wherein the strength ratio represented by breaking strength / extrusion pressure is greater than 1.90 N / MPa.
[0019] The present invention (6) is a modified polytetrafluoroethylene in combination with any one of the present inventions (1) to (5), which is in the form of a powder.
[0020] The present invention (7) is a modified polytetrafluoroethylene in combination with any one of the present inventions (1) to (6), which is in the form of a fine powder.
[0021] Effects of the Invention
[0022] According to the present invention, it is possible to provide modified polytetrafluoroethylene having a low extrusion pressure despite high breaking strength. DETAILED DESCRIPTION
[0023] Polytetrafluoroethylene (PTFE) is modified PTFE, and primary particle size decreases, and extrusion pressure has a tendency to increase thereupon. Usually, if extrusion pressure is increased, fracture strength can be increased, but the paste extrudate hardens, and the moldability of the extrudate has a tendency to deteriorate. In addition, if the paste extrudate is harder, it becomes uneven in post-processing, and may break during processing such as stretching, so it is expected that extrusion pressure is lower.
[0024] However, as a result of intensive research, it was found that, contrary to common technical knowledge, PTFE having a high breaking strength but a low extrusion pressure could be obtained by using chlorotrifluoroethylene as a modifying monomer and controlling the polymerization conditions to produce a stretchable high molecular weight body.
[0025] The present invention is described in detail below.
[0026] The present invention provides a modified PTFE which can be stretched and contains tetrafluoroethylene (TFE) units and chlorotrifluoroethylene (CTFE) units, wherein the amount of the CTFE units is 1.0 mass % or less relative to the total polymer units.
[0027] Since the modified PTFE of the present invention has the above-mentioned structure, it has a low extrusion pressure despite its high breaking strength and is excellent in moldability.
[0028] It is speculated that the structure of CTFE is similar to that of TFE, and the crystal structure of PTFE is not easily collapsed, thereby suppressing the increase in extrusion pressure.
[0029] The modified PTFE of the present invention comprises TFE units (polymerized units based on TFE) and CTFE units (polymerized units based on CTFE), and the amount of the CTFE units is 1.0 mass % or less based on all polymerized units.
[0030] The content of the TFE unit in the modified PTFE may be 99.0% by mass or more.
[0031] The modified PTFE may further contain polymerized units based on modifying monomers other than TFE and CTFE (other modifying monomer units), may consist of only TFE units and CTFE units, and preferably consists of only TFE units and CTFE units.
[0032] Examples of the other modified monomers include fluorinated olefins such as hexafluoropropylene; fluorinated (alkyl vinyl ethers) having an alkyl group containing 1 to 5 carbon atoms, particularly 1 to 3 carbon atoms; cyclic fluorinated monomers such as fluorodioxole; perfluoroalkylethylene; ω-hydrogenated perfluoroolefins, etc.
[0033] The content of the other modified monomer units is preferably less than 1.0% by mass, more preferably 0.1% by mass or less, based on the total polymerized units.
[0034] The total amount of the CTFE units and the other modifying monomer units is preferably 1.0% by mass or less based on the total polymerized units.
[0035] The content of the CTFE unit is 1.0% by mass or less relative to the total polymerized units. From the perspective of further reducing the extrusion pressure and further improving the breaking strength, the content of the CTFE unit is preferably 0.50% by mass or less, more preferably 0.30% by mass or less, further preferably 0.20% by mass or less, further more preferably 0.10% by mass or less, further more preferably 0.08% by mass or less relative to the total polymerized units.
[0036] The content of the CTFE unit may be 0.0001% by mass or more, or 0.001% by mass or more, based on the total polymer units.
[0037] In this specification, the CTFE unit refers to a part of the molecular structure of modified PTFE and is a part derived from CTFE.
[0038] The content of each polymerized unit described above can be calculated by appropriately combining NMR, FT-IR, elemental analysis, and fluorescent X-ray analysis according to the type of monomer.
[0039] The modified PTFE of the present invention can be stretched. The conventional CTFE-modified PTFE described in Patent Document 1 for the purpose of improving paste extrudability is not sufficiently high in molecular weight and cannot be stretched.
[0040] In this specification, "capable of stretching" is judged by the following criteria.
[0041] The strips obtained by extrusion of the paste described later are dried at 230°C for 30 minutes, and the lubricant is removed from the strips. Next, the strips (extruded molded bodies) are cut into appropriate lengths, and each end is fixed to the chucks in a manner that the chuck spacing is 2.0 inches (51 mm), and heated to 300°C in an air circulation oven. Next, the chucks are separated at the desired speed (stretching speed) to a separation distance equivalent to the desired stretching (total stretching), and a stretching test is performed. This stretching method is essentially in accordance with the method disclosed in the specification of U.S. Patent No. 4,576,869, except that the extrusion speed (51 cm / minute instead of 84 cm / minute) is different. "Stretching" refers to the increase in length caused by extension, and is usually expressed in relation to the original length. In the above-mentioned production method, the above-mentioned stretching speed is 1000% / second, and the above-mentioned total stretching is 2400%. The situation in which there is no breakage until the above-mentioned stretching is completed is judged to be able to stretch.
[0042] The modified PTFE of the present invention is preferably not broken even after the stretching is completed when a stretching test is conducted under the conditions of a stretching speed of 100% / sec and a total stretching of 2400% in the above-mentioned production method.
[0043] The breaking strength of the modified PTFE of the present invention is preferably 20.0 N or more, more preferably 25.0 N or more, further preferably 30.0 N or more, still more preferably 32.0 N or more, and still more preferably 35.0 N or more. The higher the breaking strength, the better, and it can be 100.0 N or less, 80.0 N or less, or 50.0 N or less.
[0044] The above-mentioned breaking strength is a value obtained by the following method.
[0045] The tensile bar (made by stretching the bar) obtained in the tensile test at a tensile speed of 100% / sec was clamped and fixed in a movable jaw with a gauge length of 5.0 cm, and a tensile test was performed at 25°C at a speed of 300 mm / min, and the strength at break was measured as the breaking strength.
[0046] The extrusion pressure of the modified PTFE of the present invention is preferably below 50.0MPa, more preferably below 40.0MPa, further preferably below 30.0MPa, and further more preferably below 25.0MPa, and further more preferably below 23.0MPa, and further more preferably below 21.0MPa, and particularly preferably below 20.0MPa. The extrusion pressure can be above 5.0MPa, can be above 10.0MPa, can be above 12.0MPa, can be above 15.0MPa, and can also be above 17.0MPa.
[0047] The extrusion pressure is a value obtained by the following method.
[0048] 21.7 g of lubricant (trade name: Isopar H (registered trademark), manufactured by Exxon) was added to 100 g of modified PTFE powder, and mixed at room temperature for 3 minutes to obtain a PTFE fine powder mixture. Next, the obtained PTFE fine powder mixture was placed at room temperature (25°C) for at least 1 hour before extrusion, and then paste extruded through a hole (diameter 2.5 mm, land length 11 mm, introduction angle 30°) at room temperature with a reduction ratio of 100:1 (ratio of the cross-sectional area of the inlet of the die to the cross-sectional area of the outlet) to obtain a uniform beading (extruded molded body). The extrusion speed, i.e., the punch speed, was set to 20 inches / minute (51 cm / minute). The extrusion pressure is a value obtained by measuring the load when the extrusion load reaches a balanced state in the paste extrusion and dividing it by the cross-sectional area of the barrel used in the paste extrusion.
[0049] The strength ratio represented by the breaking strength (N) / extrusion pressure (MPa) of the modified PTFE of the present invention is preferably greater than 1.90 N / MPa, more preferably 1.95 N / MPa or more, further preferably 2.00 N / MPa or more, still more preferably 2.05 N / MPa or more, and particularly preferably 2.10 N / MPa or more. The higher the strength ratio, the better, and it can be 5.00 N / MPa or less, or 4.00 N / MPa or less.
[0050] A higher strength ratio means a higher breaking strength and a lower extrusion pressure.
[0051] The above-mentioned breaking strength and extrusion pressure are values obtained by the above-mentioned method.
[0052] From the viewpoint of excellent stretchability, the standard specific gravity (SSG) of the modified PTFE of the present invention is more preferably 2.180 or less, further preferably 2.170 or less, and particularly preferably 2.160 or less.
[0053] In addition, the standard specific gravity is preferably 2.130 or more.
[0054] The standard specific gravity is measured by a water displacement method according to ASTM D 792 using a sample molded according to ASTM D 4895.
[0055] The modified PTFE of the present invention generally has non-melt secondary processability. The non-melt secondary processability refers to the property that the melt flow rate cannot be measured at a temperature higher than the melting point according to ASTM D-1238 and D-2116, in other words, the property that it is not easy to flow even in the melting temperature region.
[0056] The modified PTFE of the present invention preferably has one or more endothermic peaks in the range of 333 to 347°C in a heat of fusion curve when the temperature is increased at a rate of 10°C / min using a differential scanning calorimeter [DSC] without a history of being heated to a temperature of 300°C or higher, and the heat of fusion at 290 to 350°C calculated from the above heat of fusion curve is 62 mJ / mg or higher.
[0057] The modified PTFE of the present invention can be produced, for example, by a production method including the step of emulsion polymerizing TFE and CTFE (and other modifying monomers as necessary).
[0058] The above-mentioned emulsion polymerization can be carried out in an aqueous medium in the presence of an anionic fluorinated surfactant and a polymerization initiator, for example.
[0059] The emulsion polymerization can be carried out as follows: an aqueous medium, the anionic fluorinated surfactant, a monomer, and other additives as needed are added to a polymerization reactor, the contents of the reactor are stirred, the reactor is maintained at a predetermined polymerization temperature, and then a predetermined amount of a polymerization initiator is added to initiate the polymerization reaction. After the polymerization reaction starts, monomers, polymerization initiators, chain transfer agents, and the surfactant can be added according to the purpose.
[0060] From the perspective of easily obtaining the above-mentioned physical properties, the CTFE concentration in the gas in the reactor at the start of polymerization (when the initiator is added) is preferably set to 0.001 mol% or more, and more preferably 0.01 mol% or more. In addition, the above concentration is preferably 3.0 mol% or less, and more preferably 1.0 mol% or less. The above-mentioned modified monomer concentration can be maintained thereafter until the end of the polymerization reaction, or pressure relief can be implemented midway. From the perspective of obtaining excellent tensile properties, CTFE is preferably added all at once before the start of polymerization, but a portion can also be added continuously or intermittently after the start of polymerization.
[0061] As the above-mentioned polymerization initiator, there is no particular limitation as long as it can generate free radicals in the polymerization temperature range, and known oil-soluble and / or water-soluble polymerization initiators can be used. Furthermore, it is also possible to combine with a reducing agent etc. to initiate polymerization in a redox form. The concentration of the above-mentioned polymerization initiator is appropriately determined according to the type of monomer, the molecular weight of the target modified PTFE, and the reaction rate.
[0062] As the polymerization initiator, an oil-soluble radical polymerization initiator or a water-soluble radical polymerization initiator can be used.
[0063] The oil-soluble free radical polymerization initiator may be a known oil-soluble peroxide, and for example, the following peroxides may be cited as representative substances: dialkyl peroxycarbonates such as diisopropyl peroxydicarbonate and di-sec-butyl peroxydicarbonate; peroxyesters such as tert-butyl peroxyisobutyrate and tert-butyl peroxypivalate; dialkyl peroxides such as di-tert-butyl peroxide; and di(ω-hydro-dodecafluoroheptanoyl) peroxide, di(ω-hydro-tetradecafluoroheptanoyl) peroxide, di(ω-hydro-hexadecanoyl) peroxide, di(perfluorobutanoyl) peroxide, di(perfluoropentanoyl) peroxide, di(perfluorohexanoyl) peroxide, di(perfluoroheptanoyl) peroxide, di(perfluorooctanoyl) peroxide. peroxide, di(perfluorononanoyl)peroxide, di(ω-chloro-hexafluorobutyryl)peroxide, di(ω-chloro-decafluorohexanoyl)peroxide, di(ω-chloro-tetrafluorooctanoyl)peroxide, ω-hydro-dodecafluoroheptanoyl-ω-hydrohexafluorononanoyl-peroxide, ω-chloro-hexafluorobutyryl-ω-chloro-decafluorohexanoyl-peroxide, ω-hydro-dodecafluoroheptanoyl-perfluorobutyryl-peroxide, di(dichloropentafluorobutyryl)peroxide, di(trichlorooctafluorohexanoyl)peroxide, di(tetrachloroundecanoyl)peroxide, di(pentachlorotetrafluorodecanoyl)peroxide, di(undecanotridodecanoyl)peroxide and the like di[perfluoro(or fluorochloro)acyl]peroxides; and the like.
[0064] As the water-soluble free radical polymerization initiator, it can be a known water-soluble peroxide, for example, ammonium salts, potassium salts, sodium salts of persulfuric acid, perboric acid, perchloric acid, perphosphoric acid, percarbonic acid, tert-butyl peroxymaleate, tert-butyl hydroperoxide, etc. It can also contain a reducing agent such as sulfites and sulfites, and its amount can be 0.1 to 20 times that of the peroxide.
[0065] The amount of water-soluble free radical polymerization initiator added is not particularly limited, and the amount (for example, a concentration of several ppm relative to water) of the degree that the polymerization rate does not significantly decrease is added once, successively, or continuously at the initial stage of polymerization. The upper limit is the range in which the polymerization reaction heat can be used to remove heat from the device surface and the reaction temperature can be increased at the same time, and the more preferred upper limit is the range in which the polymerization reaction heat can be removed from the device surface. More specifically, for example, relative to an aqueous medium, it is preferably more than 1ppm, more preferably more than 10ppm, and more preferably more than 50ppm. In addition, it is preferably less than 100000ppm, more preferably less than 10000ppm, and more preferably less than 5000ppm.
[0066] From the perspective of easily obtaining the above-mentioned physical properties, the amount of the polymerization initiator added is preferably an amount equivalent to 0.1 ppm or more, more preferably an amount equivalent to 1.0 ppm or more, and is preferably an amount equivalent to 100 ppm or less, more preferably an amount equivalent to 10 ppm or less, relative to the aqueous medium.
[0067] For example, when the polymerization is carried out at a low temperature below 30°C, it is preferred to use a redox initiator that combines an oxidant and a reductant as a polymerization initiator. As the oxidant, persulfates, organic peroxides, potassium permanganate, manganese triacetate, ammonium cerium nitrate, bromates, etc. can be mentioned. As the reductant, sulfites, bisulfites, bromates, diimides, oxalic acid, etc. can be mentioned. As persulfates, ammonium persulfate and potassium persulfate can be mentioned. As sulfites, sodium sulfite and ammonium sulfite can be mentioned. In order to increase the decomposition rate of the initiator, it is also preferred to add copper salts and iron salts to the combination of redox initiators. As copper salts, copper (II) sulfate can be mentioned, and as iron salts, iron (II) sulfate can be mentioned.
[0068] As the redox initiator, it is preferred that the oxidizing agent is permanganic acid or a salt thereof, persulfate, manganese triacetate, cerium (IV) salt, or bromic acid or a salt thereof, and the reducing agent is dicarboxylic acid or a salt thereof, or diimine.
[0069] More preferably, the oxidizing agent is permanganic acid or a salt thereof, persulfate, or bromic acid or a salt thereof, and the reducing agent is a dicarboxylic acid or a salt thereof.
[0070] Examples of the redox initiator include combinations of potassium permanganate / oxalic acid, potassium permanganate / ammonium oxalate, manganese triacetate / oxalic acid, manganese triacetate / ammonium oxalate, cerium ammonium nitrate / oxalic acid, and cerium ammonium nitrate / ammonium oxalate.
[0071] When a redox initiator is used, either the oxidant or the reductant may be placed in a polymerization vessel in advance, and then the other may be added continuously or intermittently to initiate polymerization. For example, when potassium permanganate / ammonium oxalate is used, it is preferred that ammonium oxalate is placed in the polymerization vessel and potassium permanganate is continuously added thereto.
[0072] It should be noted that, in the redox initiator of the present specification, when "potassium permanganate / ammonium oxalate" is described, it means a combination of potassium permanganate and ammonium oxalate. The same applies to other compounds.
[0073] The redox initiator is particularly preferably a combination of an oxidizing agent which is a salt and a reducing agent which is a salt.
[0074] For example, the oxidizing agent as the salt is more preferably at least one selected from the group consisting of persulfate, permanganate, cerium (IV) salt and bromate, further preferably permanganate, and particularly preferably potassium permanganate.
[0075] The reducing agent for the salt is more preferably at least one selected from the group consisting of oxalates, malonates, succinates, glutarates and bromates, further preferably oxalates, and particularly preferably ammonium oxalate.
[0076] Specifically, the redox initiator is preferably at least one selected from the group consisting of potassium permanganate / oxalic acid, potassium permanganate / ammonium oxalate, potassium bromate / ammonium sulfite, manganese triacetate / ammonium oxalate and cerium ammonium nitrate / ammonium oxalate, more preferably at least one selected from the group consisting of potassium permanganate / oxalic acid, potassium permanganate / ammonium oxalate, potassium bromate / ammonium sulfite and cerium ammonium nitrate / ammonium oxalate, and further preferably potassium permanganate / oxalic acid.
[0077] When a redox initiator is used, the oxidant and the reducing agent may be added at once at the beginning of the polymerization, the reducing agent may be added at once and the oxidant may be added continuously at the beginning of the polymerization, the oxidant may be added at once and the reducing agent may be added continuously at the beginning of the polymerization, or both the oxidant and the reducing agent may be added continuously.
[0078] When a redox initiator is used as a polymerization initiator, the amount of the oxidant added is preferably 5 ppm or more, more preferably 10 ppm or more, and preferably 10000 ppm or less, and more preferably 1000 ppm or less, relative to the aqueous medium. The amount of the reducing agent added is preferably 5 ppm or more, more preferably 10 ppm or more, and preferably 10000 ppm or less, and more preferably 1000 ppm or less.
[0079] From the aspect of easily obtaining modified PTFE suitable for stretching purposes, the addition amount of the oxidant is preferably 0.1 ppm or more, more preferably 1.0 ppm or more, and preferably 100 ppm or less, and more preferably 10 ppm or less, relative to the aqueous medium. The addition amount of the reducing agent is preferably 0.1 ppm or more, more preferably 1.0 ppm or more, and preferably 100 ppm or less, and more preferably 10 ppm or less.
[0080] When a redox initiator is used in the emulsion polymerization, the polymerization temperature is preferably 100°C or lower, more preferably 95°C or lower, and further preferably 90°C or lower. It is preferably 10°C or higher, more preferably 20°C or higher, and further preferably 30°C or higher.
[0081] From the viewpoint of easily obtaining the above-mentioned physical properties, the polymerization initiator is preferably a water-soluble radical polymerization initiator or a redox initiator.
[0082] The aqueous medium is a reaction medium for polymerization and is a liquid containing water. The aqueous medium is not particularly limited as long as it contains water, and may contain water and a non-fluorinated organic solvent such as alcohol, ether, or ketone and / or a fluorinated organic solvent having a boiling point of 40° C. or less.
[0083] In the emulsion polymerization, a nucleating agent, a chain transfer agent, a buffer, a pH adjuster, a stabilizing aid, a dispersion stabilizer, a radical scavenger, a decomposing agent of a polymerization initiator, and the like may be used as necessary.
[0084] The emulsion polymerization is preferably carried out by adding a nucleating agent for the purpose of adjusting the particle size. The nucleating agent is preferably added before the start of the polymerization reaction.
[0085] As the nucleating agent, a known nucleating agent can be used, and for example, at least one selected from the group consisting of fluoropolyethers, nonionic surfactants, and chain transfer agents is preferred, and a nonionic surfactant is more preferred.
[0086] Examples of the fluorinated polyether include perfluoropolyether (PFPE) acid and salts thereof.
[0087] The above-mentioned perfluoropolyether (PFPE) acid or its salt may have any chain structure in which oxygen atoms in the main chain of the molecule are separated by saturated fluorocarbon groups having 1 to 3 carbon atoms. In addition, two or more fluorocarbon groups may exist in the molecule. A representative structure has a repeating unit represented by the following formula.
[0088] (-CFCF3-CF2-O-) n
[0089] (-CF2-CF2-CF2-O-) n
[0090] (-CF2-CF2-O-) n -(-CF2-O-) m
[0091] (-CF2-CFCF3-O-) n -(-CF2-O-) m
[0092] These structures are described by Kasai in J. Appl. Polymer Sci. 57, 797 (1995). As disclosed in the document, the PFPE acid or its salt may have a carboxylic acid group or its salt at one or both ends. In addition, the PFPE acid or its salt may have a sulfonic acid, phosphonic acid group or its salt at one or both ends. In addition, the PFPE acid or its salt may have different groups at each end. For monofunctional PFPE, the other end of the molecule is usually perfluorinated and may also contain hydrogen or chlorine atoms. The PFPE acid or its salt has at least 2 ether oxygens, preferably at least 4 ether oxygens, and more preferably at least 6 ether oxygens. Preferably, at least one of the fluorocarbon groups separated by the ether oxygen, more preferably at least two of such fluorocarbon groups have 2 or 3 carbon atoms. More preferably, at least 50% of the fluorocarbon groups separated by the ether oxygen have 2 or 3 carbon atoms. In addition, preferably, the PFPE acid or its salt has a total of at least 15 carbon atoms, for example, the preferred minimum value of n or n+m in the repeating unit structure is at least 5. Two or more PFPE acids or salts thereof having an acid group at one or both ends can be used in the production method of the present invention. The PFPE acid or salt thereof preferably has a number average molecular weight of less than 6000 g / mol.
[0093] From the aspect that the modified PTFE can be further high molecular weighted and the stretchability can be improved, the above-mentioned emulsion polymerization is preferably carried out by adding a free radical scavenger or a decomposition agent of a polymerization initiator. The above-mentioned free radical scavenger or the decomposition agent of a polymerization initiator is preferably added after the polymerization reaction starts, preferably before 10% by mass or more, preferably 20% by mass or more of the total TFE consumed in the polymerization reaction is polymerized, and in addition, preferably before 50% by mass or less, preferably 40% by mass or less is polymerized. In the case of performing the pressure relief and re-pressurization described later, it is preferably added afterwards.
[0094] As the free radical scavenger, a compound that is added to the free radical in the polymerization system or has no reinitiation ability after chain transfer is used. Specifically, a compound having the following functions is used: it is easy to undergo a chain transfer reaction with a primary free radical or a growing free radical, and then generate a stable free radical that does not react with the monomer, or it is easy to undergo an addition reaction with a primary free radical or a growing free radical to generate a stable free radical.
[0095] The activity of a substance generally referred to as a chain transfer agent is characterized by a chain transfer constant and a reinitiation efficiency. Among chain transfer agents, a substance having a reinitiation efficiency of substantially 0% is referred to as a free radical scavenger.
[0096] The radical scavenger can be, for example, a compound whose chain transfer constant with TFE at the polymerization temperature is greater than the polymerization rate constant and whose reinitiation efficiency is substantially zero%. "Substantially zero% reinitiation efficiency" means that the generated radicals make the radical scavenger a stable radical.
[0097] Preferred are compounds having a chain transfer constant (Cs) with TFE at the polymerization temperature (=chain transfer rate constant (kc) / polymerization rate constant (kp)) greater than 0.1, and the chain transfer constant (Cs) of the above-mentioned compound is more preferably 0.5 or more, further preferably 1.0 or more, further preferably 5.0 or more, and particularly preferably 10 or more.
[0098] The radical scavenger is preferably at least one selected from the group consisting of, for example, aromatic hydroxy compounds, aromatic amines, N,N-diethylhydroxylamine, quinone compounds, terpenes, thiocyanates, and cupric chloride (CuCl 2 ).
[0099] Examples of the aromatic hydroxy compound include unsubstituted phenol, polyphenol, salicylic acid, m-salicylic acid or p-salicylic acid, gallic acid, and naphthol.
[0100] Examples of the unsubstituted phenol include o-nitrophenol, m-nitrophenol, p-nitrophenol, o-aminophenol, m-aminophenol, p-aminophenol, p-nitrosophenol, etc. Examples of the polyphenol include catechol, resorcinol, hydroquinone, pyrogallol, pyrogallol, naphthol resorcinol, etc.
[0101] Examples of the aromatic amines include o-phenylenediamine, m-phenylenediamine, p-phenylenediamine, and benzidine.
[0102] Examples of the quinone compound include o-benzoquinone, m-benzoquinone, p-benzoquinone, 1,4-naphthoquinone, and alizarin.
[0103] Examples of the thiocyanate include ammonium thiocyanate (NH4SCN), potassium thiocyanate (KSCN), and sodium thiocyanate (NaSCN).
[0104] As the radical scavenger, an aromatic hydroxy compound is preferred, an unsubstituted phenol or a polyphenol is more preferred, and hydroquinone is further preferred.
[0105] From the aspect of appropriately reducing the standard specific gravity, the amount of the free radical scavenger added is preferably an amount equivalent to 3% to 500% (molar basis) of the polymerization initiator concentration. A more preferred lower limit is 10% (molar basis), and a further preferred upper limit is 400% (molar basis), and a further preferred upper limit is 300% (molar basis).
[0106] As the decomposition agent of the above-mentioned polymerization initiator, any compound capable of decomposing the polymerization initiator used may be used, for example, at least one selected from the group consisting of sulfites, bisulfites, bromates, diimides, diimide salts, oxalic acid, oxalates, copper salts and iron salts. As sulfites, sodium sulfite and ammonium sulfite can be mentioned. As copper salts, copper (II) sulfate can be mentioned, and as iron salts, iron (II) sulfate can be mentioned.
[0107] From the aspect of appropriately reducing the standard specific gravity, the amount of the above-mentioned decomposition agent added is preferably an amount equivalent to 3% to 500% (molar basis) of the initiator concentration. A more preferred lower limit is 10% (molar basis), and a further preferred upper limit is 400% (molar basis), and a further preferred upper limit is 300% (molar basis).
[0108] In the above-mentioned emulsion polymerization, the polymerization temperature and polymerization pressure are appropriately determined according to the type of monomer used, the molecular weight of the target modified PTFE, and the reaction rate. Usually, the polymerization temperature is 5°C to 150°C, preferably above 10°C, more preferably above 30°C, and further preferably above 50°C. In addition, it is more preferably below 120°C, and further preferably below 100°C.
[0109] The polymerization pressure is 0.05 MPaG to 10 MPaG. The polymerization pressure is more preferably 0.3 MPaG or more, and even more preferably 0.5 MPaG or more. Furthermore, the polymerization pressure is more preferably 5.0 MPaG or less, and even more preferably 3.0 MPaG or less.
[0110] In the emulsion polymerization, after the modified monomer is added to the polymerization vessel, it is preferred not to release the pressure before the polymerization is completed. This allows the modified monomer to remain in the system until the end of the polymerization, and can further improve the breaking strength of the obtained modified PTFE.
[0111] The production method may include a step of precipitating the aqueous dispersion to obtain a wet powder of the modified PTFE. The precipitation may be performed by a known method.
[0112] The manufacturing method may include a step of drying the wet powder. The drying is usually carried out by vacuum, high frequency, hot air and the like while keeping the wet powder in a state that is not too fluid, preferably in a static state. Friction between powders, especially at high temperatures, usually has an adverse effect on fine powder PTFE. This is because the particles composed of PTFE have the property of simply fibrillating even when subjected to a small shear force, and losing the original stable particle structure. From the perspective of further improving the breaking strength, the drying temperature may be above 10°C, preferably above 100°C, more preferably above 150°C, more preferably above 170°C, further more preferably above 190°C, further more preferably above 210°C, further more preferably above 230°C, and particularly preferably above 250°C. In addition, from the perspective of further reducing the extrusion pressure, the drying temperature may be below 300°C, preferably below 250°C, more preferably below 230°C, further preferably below 210°C, further more preferably below 190°C, and particularly preferably below 170°C. In order to further improve the above-mentioned strength ratio, it is preferable to perform appropriate adjustment within this temperature range.
[0113] The modified PTFE of the present invention is preferably in the form of powder, more preferably in the form of fine powder.
[0114] The modified PTFE of the present invention can also be provided in the form of an aqueous dispersion. An aqueous dispersion containing particles of the modified PTFE of the present invention is also a preferred embodiment of the present invention.
[0115] The average primary particle size of the modified PTFE of the present invention is preferably 500 nm or less, more preferably 350 nm or less, further preferably 300 nm or less, particularly preferably 280 nm or less, and is preferably 100 nm or more, more preferably 150 nm or more, further preferably 170 nm or more, particularly preferably 200 nm or more.
[0116] The above average primary particle size is measured by the following method.
[0117] The modified PTFE aqueous dispersion was diluted with water until the solid content concentration reached 0.15% by mass, and the transmittance of the projected light at 550 nm relative to the unit length of the obtained diluted emulsion was measured, and the number-based length average particle size determined by measuring the directional diameter using a transmission electron microscope photograph was prepared to prepare a calibration curve. Using this calibration curve, the number average particle size was determined from the measured transmittance of the projected light at 550 nm of each sample as the average primary particle size.
[0118] The average aspect ratio of the primary particles of the modified PTFE of the present invention may be 2.0 or less, preferably 1.8 or less, more preferably 1.7 or less, further preferably 1.6 or less, further preferably 1.5 or less, further preferably 1.4 or less, particularly preferably 1.3 or less, particularly preferably 1.2 or less, and most preferably 1.1 or less. In addition, the above average aspect ratio may be 1.0 or more.
[0119] The average aspect ratio is determined by observing fluororesin powder or an aqueous fluororesin dispersion diluted to a solid content concentration of about 1% by mass using a scanning electron microscope (SEM), performing image processing on 200 or more particles randomly selected, and calculating the average ratio of the major axis to the minor axis.
[0120] The average secondary particle size of the modified PTFE of the present invention is preferably 100 μm or more, more preferably 200 μm or more, further preferably 300 μm or more, and is preferably 2000 μm or less, more preferably 1000 μm or less, further preferably 800 μm or less, particularly preferably 700 μm or less.
[0121] The above average secondary particle size is measured in accordance with JIS K6891.
[0122] The modified PTFE of the present invention is particularly useful as a raw material for an elongated body. An elongated body formed from the modified PTFE of the present invention is also a preferred embodiment of the present invention.
[0123] The above-mentioned stretched product can be obtained by stretching the modified PTFE of the present invention.
[0124] The stretched body is also preferably in the shape of a film, a tube, a fiber, or a rod.
[0125] When the stretched body is a film (stretched film or porous film), it can be stretched by a known PTFE stretching method.
[0126] Preferably, a sheet-shaped or rod-shaped paste extrudate is roll-stretched in the extrusion direction to obtain a uniaxially stretched film.
[0127] Furthermore, by stretching in the width direction using a tenter or the like, a biaxially stretched film can also be obtained.
[0128] It is also preferred to perform a semi-firing treatment before stretching.
[0129] The stretched body can be made into a porous body with high porosity, and can be suitably used as a filter material for various microfiltration filters such as air filters and reagent filters, a supporting material for polymer electrolyte membranes, and the like.
[0130] Furthermore, it is also useful as a material for products used in the fields of fibers, medicine, electrochemistry, sealing materials, air filtration, ventilation / internal pressure regulation, liquid filtration, and general consumables.
[0131] Specific uses are exemplified below.
[0132] Electrochemical field
[0133] Dielectric material prepreg, EMI shielding material, heat transfer material, etc. More specifically, printed circuit board, electromagnetic shielding material, insulating heat transfer material, insulating material, etc.
[0134] Sealing material field
[0135] Gaskets, sealing pads, pump diaphragms, pump tubes, sealing materials for aircraft, etc.
[0136] Air filtration field
[0137] ULPA filter (for semiconductor manufacturing), HEPA filter (for hospital and semiconductor manufacturing), cylindrical cartridge filter (for industrial use), bag filter (for industrial use), heat-resistant bag filter (for exhaust gas treatment), heat-resistant pleated filter (for exhaust gas treatment), SINBRAN filter (for industrial use), catalytic filter (for exhaust gas treatment), filter with adsorbent (for HDD assembly), ventilation filter with adsorbent (for HDD assembly), ventilation filter (for HDD assembly, etc.), filter for vacuum cleaner (for vacuum cleaner), general-purpose multilayer felt, cartridge filter for GT (for GT interchangeable parts), cooling filter (for electronic equipment housing), etc.
[0138] Ventilation / internal pressure adjustment area
[0139] Freeze-drying materials such as freeze-drying containers, automotive ventilation materials suitable for electronic circuits or lamps, container uses such as container covers, protective ventilation uses for electronic devices including small terminals such as tablet terminals and mobile phone terminals, medical ventilation uses, etc.
[0140] Liquid filtration field
[0141] Semiconductor liquid filters (for semiconductor manufacturing), hydrophilic PTFE filters (for semiconductor manufacturing), filters suitable for chemicals (for reagent processing), filters for pure water production lines (for pure water production), backwash type liquid filtration filters (for industrial wastewater treatment), etc.
[0142] General consumables field
[0143] Clothing, cable guide tubes (removable wires suitable for motorcycles), motorcycle clothing, cast pads (medical protective gear), vacuum cleaner filters, bagpipes (musical instruments), cables (signal cables for guitars, etc.), strings (for stringed instruments), etc.
[0144] Fiber field
[0145] PTFE fiber (fibrous material), sewing thread (fabric), knitting thread (fabric), rope, etc.
[0146] Medical field
[0147] Embedded products (stretchable products), artificial blood vessels, catheters, general surgery (tissue reinforcement materials), head and neck products (dura mater substitutes), oral health (tissue regeneration medicine), plastic surgery (bandages), etc.
[0148] The modified PTFE of the present invention can also be suitably used in various additives such as dust-proof additives, anti-drip agents, adhesives for batteries, coating applications, and glass cloth impregnation processing applications.
[0149] In addition, the aqueous dispersion of particles containing the modified PTFE of the present invention is used to produce an infiltrate such as roofing materials by, for example, impregnating it in a surface coating agent for cooking utensils, glass fiber, carbon fiber, Kebler (registered trademark) fiber, etc., and is also used in the formation of a film formed by coating and firing the coated object in applications such as high-frequency printed substrates, conveyor belts, and sealing gaskets, and can be applied to various applications.
[0150] Although the embodiments have been described above, it should be understood that various changes may be made to the embodiments and details without departing from the spirit and scope of the claims.
[0151] Example
[0152] Next, the present invention will be described in more detail with reference to Examples, but the present invention is not limited to these Examples.
[0153] Various physical properties were measured by the following methods.
[0154] Average primary particle size
[0155] The modified PTFE aqueous dispersion was diluted with water until the solid content concentration reached 0.15% by mass, and the transmittance of the projected light at 550 nm relative to the unit length of the obtained diluted emulsion was measured, and the number-based length average particle size determined by measuring the directional diameter using a transmission electron microscope photograph was prepared to prepare a calibration curve. Using this calibration curve, the number average particle size was determined from the measured transmittance of the projected light at 550 nm of each sample as the average primary particle size.
[0156] Polymer solid content
[0157] 1 g of the modified PTFE aqueous dispersion was dried in a blower dryer at 150° C. for 60 minutes, and the ratio of the mass of the heating residue to the mass of the aqueous dispersion (1 g) was expressed as a percentage.
[0158] Content of modified monomer
[0159] The CTFE content was determined as follows: PTFE powder was compression molded into a film disk, and the film disk was subjected to FT-IR measurement to obtain the infrared absorbance at 957 cm -1 Absorbance / 2360cm -1 The absorbance ratio is multiplied by 0.58.
[0160] Standard Specific Gravity (SSG)
[0161] The measurement was performed by the water displacement method according to ASTM D 792 using a sample formed according to ASTM D 4895.
[0162] Endothermic peak temperature
[0163] The endothermic peak temperature is the temperature corresponding to the minimum point in the heat of fusion curve when the temperature of PTFE that has no history of heating to a temperature of 300° C. or higher is increased at a rate of 10° C. / min using a differential scanning calorimeter [DSC].
[0164] Extrusion pressure
[0165] 21.7 g of lubricant (trade name: Isopar H (registered trademark), manufactured by Exxon) was added to 100 g of modified PTFE powder, and mixed at room temperature for 3 minutes to obtain a PTFE fine powder mixture. Next, the obtained PTFE fine powder mixture was placed at room temperature (25°C) for at least 1 hour before extrusion, and then paste extruded through a hole (diameter 2.5 mm, land length 11 mm, introduction angle 30°) at room temperature with a reduction ratio of 100:1 (ratio of the cross-sectional area of the inlet of the die to the cross-sectional area of the outlet) to obtain a uniform beading (extruded molded body). The extrusion speed, i.e., the punch speed, was set to 20 inches / minute (51 cm / minute). The extrusion pressure is a value obtained by measuring the load when the extrusion load reaches a balanced state in the paste extrusion and dividing it by the cross-sectional area of the barrel used in the paste extrusion.
[0166] Tensile test
[0167] The strips extruded from the paste are heated at 230°C for 30 minutes to remove the lubricant from the strips. Next, the strips (extruded molded bodies) are cut into appropriate lengths, each end is fixed to the chucks at intervals of 2.0 inches (51 mm) between the chucks, and heated to 300°C in an air circulating oven. Next, the chucks are separated at the desired speed (stretching speed) to a separation distance corresponding to the desired stretching (total stretching), and a stretching test is performed. This stretching method is essentially in accordance with the method disclosed in the specification of U.S. Patent No. 4,576,869, except that the extrusion speed (51 cm / min instead of 84 cm / min) is different. "Stretching" refers to the increase in length caused by extension, and is usually expressed in relation to the original length. In the above-mentioned production method, the above-mentioned stretching speed is 100% / sec, and the above-mentioned total stretching is 2400%.
[0168] Breaking strength
[0169] The tensile bar obtained in the above tensile test (made by stretching a bar) was clamped and fixed in movable jaws with a gauge length of 5.0 cm, and a tensile test was performed at 25°C and a speed of 300 mm / min. The strength at break was measured as the breaking strength.
[0170] Strength ratio
[0171] Calculated from breaking strength (N) / extrusion pressure (MPa).
[0172] Synthesis example 1
[0173] A white solid A was obtained by the method described in Synthesis Example 1 of International Publication No. 2021 / 045228.
[0174] Example 1
[0175] 3600g of deionized water, 180g of paraffin, 5.4g of white solid A, and 26.5mg of oxalic acid were added to a SUS reactor with a stirrer having a content of 6L. Then, the contents of the reactor were heated to 70°C while being sucked, and tetrafluoroethylene (TFE) was purged to remove oxygen in the reactor, and the contents were stirred. 2.60g of chlorotrifluoroethylene (CTFE) was pressed into the reactor with TFE, and then TFE was added to make it 2.70MPaG. A potassium permanganate aqueous solution in which 3.4mg of potassium permanganate was dissolved in deionized water was continuously added to the reactor as an initiator. After the initiator was injected, a decrease in pressure occurred, and the start of polymerization was observed. TFE was added to the reactor, and the pressure was kept constant at 2.70MPaG. At the moment when the amount of TFE fed reached 430g, the potassium permanganate aqueous solution was stopped. At the moment when the amount of TFE fed reached 1660g, the supply of TFE was stopped, stirring was stopped, and the reaction was terminated. After that, the pressure in the reactor was vented to normal pressure, nitrogen was replaced, and the contents were taken out of the reactor and cooled. The paraffin was removed to obtain a PTFE aqueous dispersion. The solid content concentration of the obtained PTFE aqueous dispersion was 31.4% by mass and the average primary particle size was 248 nm.
[0176] The obtained PTFE aqueous dispersion was diluted to a solid content concentration of 13% by mass, and vigorously stirred in a container with a stirrer to solidify. The solidified wet powder was taken out and dried at 210°C for 18 hours to obtain PTFE powder. Various physical properties of the obtained PTFE powder were measured. The results are shown in Table 1.
[0177] Example 2
[0178] The polymerization was carried out under the same conditions as in Example 1 except that the CTFE feed amount was 1.28 g, the potassium permanganate feed amount was changed to 3.87 mg, and the final TFE amount was changed to 1790 g, to obtain a PTFE aqueous dispersion. The obtained PTFE aqueous dispersion had a solid content concentration of 33.0% by mass and an average primary particle size of 263 nm.
[0179] Using the obtained PTFE aqueous dispersion, a PTFE powder was obtained in the same manner as in Example 1. Various physical properties of the obtained PTFE powder were measured. The results are shown in Table 1.
[0180] Comparative Example 1
[0181] Except that CTFE was not added and the amount of succinic acid added was changed to 0.108 g, the amount of potassium permanganate added was changed to 3.5 mg, and the final amount of TFE added was changed to 1500 g, polymerization was carried out under the same conditions as in Example 1 to obtain a PTFE aqueous dispersion. The obtained PTFE aqueous dispersion had a solid content concentration of 29.5% by mass and an average primary particle size of 380 nm.
[0182] Using the obtained PTFE aqueous dispersion, a PTFE powder was obtained in the same manner as in Example 1. Various physical properties of the obtained PTFE powder were measured. The results are shown in Table 1.
[0183] [Table 1]
[0184]
Claims
1. A modified polytetrafluoroethylene capable of being stretched, comprising tetrafluoroethylene units and chlorotrifluoroethylene units, wherein the amount of the chlorotrifluoroethylene units is 1.0% by mass or less relative to all polymerized units.
2. The modified polytetrafluoroethylene according to claim 1, wherein The breaking strength is 20.0N or more.
3. The modified polytetrafluoroethylene according to claim 1 or 2, wherein: The extrusion pressure is 5 MPa or more.
4. The modified polytetrafluoroethylene according to any one of claims 1 to 3, wherein The extrusion pressure is 50 MPa or less.
5. The modified polytetrafluoroethylene according to any one of claims 1 to 4, wherein The strength ratio represented by breaking strength / extrusion pressure was greater than 1.90 N / MPa.
6. The modified polytetrafluoroethylene according to any one of claims 1 to 5, which is in the form of powder.
7. The modified polytetrafluoroethylene according to any one of claims 1 to 6, which is in the form of fine powder.
Citation Information
Patent Citations
Henseitetorafuruoroechirenjugotai no seizohoho
JP1976036291A
Polymerization of tetrafluoroethylene
JP2000143707A
Tetrafluoroethylene fine powder and preparation thereof
US4576869A
Aqueous polytetrafluoroethylene emulsion, and polytetrafluoroethylene fine powder and porous material produced from the same
WO2007046345A1
Polytetrafluoroethylene and method for producing same
WO2010113950A1